Deutetrabenazine in the treatment of Huntington's disease. (February 2019) - Richard, Alby; Frank, Samuel
Deutetrabenazine (DTBZ) is a US FDA-approved treatment for chorea in Huntington's disease. The substitution of deuterium for hydrogen at specific positions imparts a longer half-life on DTBZ, allowing for less-frequent daily dosing. As a reversible vesicular monoamine transporter Type 2 inhibitor, DTBZ depletes monoamines at presynaptic nerve terminals. DTBZ significantly improved chorea in Huntington's disease patients compared with placebo. This effect continued in an ongoing open-label extension study in the cohort who switched from tetrabenazine to DTBZ. Whereas there are currently no head-to-head studies to adequately compare safety profiles between tetrabenazine and DTBZ, an indirect comparison study suggested that the tolerability profile of DTBZ was similar to placebo. In fact, there are currently no direct comparisons between vesicular monoamine transporter Type 2 inhibitors in humans. This review will explore DTBZ's pharmacological properties, drug interactions, administration and efficacy.